miR-146a targets Fos expression in human cardiac cells - Xavier Palomer; Eva Capdevila-Busquets; Gaia Botteri; Mercy M. Davidson; Cristina Rodríguez; José Martínez-González; Francisco Vidal; Emma Barroso; Tung O. Chan; Arthur M. Feldman; Manuel Vázquez-Carrera (The Company of Biologists, 2015)
miR-146a is a microRNA whose transcript levels are induced in the heart upon activation of NF-κB, a transcription factor induced by pro-inflammatory molecules (such as TNF-α) that is strongly related to the pathogenesis of cardiac disorders. The main goal of this study consisted of studying new roles of miR-146a in cardiac pathological processes caused by the pro-inflammatory cytokine TNF-α. Our results demonstrate that miR-146a transcript levels were sharply increased in cardiac ventricular tissue of transgenic mice with specific overexpression of TNF-α in the heart, and also in a cardiomyocyte cell line of human origin (AC16) exposed to TNF-α. Among all the in silico predicted miR-146a target genes, Fos mRNA and protein levels notably decreased after TNF-α treatment or miR-146a overexpression. These changes correlated with a diminution in the DNA-binding activity of AP-1, the Fos-containing transcription factor complex. Interestingly, AP-1 inhibition was accompanied by a reduction in matrix metalloproteinase (MMP)-9 mRNA levels in human cardiac cells. The specific regulation of this MMP by miR-146a was further confirmed at the secretion and enzymatic activity levels, as well as after anti-miR-mediated miR-146a inhibition. The results reported here demonstrate that Fos is a direct target of miR-146a activity and that downregulation of the Fos-AP-1 pathway by miR-146a has the capacity to inhibit MMP-9 activity. Given that MMP-9 is an AP-1 target gene involved in cardiac remodeling, myocardial dysfunction and progression of heart failure, these findings suggest that miR-146a might be a new and promising therapeutic tool for treating cardiac disorders associated with enhanced inflammation in the heart.